Kināyah Dan Ṣarīḥ Dalam Penafsiran Al-Qur’an: Studi Perbandingan Tinjauan Balaghah Arab dan Semiotika Barat - Muhammad Nur; Wawan Susanto (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2025)
This study examines the comparative interpretation of ṣarīḥ (explicit) and kināyah (implicit) in the Qur'an through two main approaches, namely classical Arabic balaghah and modern Western semiotic theory. This study uses a qualitative-descriptive-comparative approach by analyzing three selected verses, namely QS. Al-Baqarah: 183, QS. Al-Baqarah: 223, and QS. An-Nūr: 31. The purpose of this study is to explore how literal and symbolic meanings are constructed in Islamic sacred texts. The results show that ṣarīḥ lafaz are generally used in legal contexts, with a strict and direct meaning structure. In contrast, kināyah lafaz tend to be used to convey social and ethical values through symbolic and contextual language styles. The balaghah approach emphasizes aesthetic and rhetorical aspects, while the semiotic approach-especially from the thoughts of Ferdinand de Saussure, Charles Sanders Peirce, and Roland Barthes-opens up room for interpretation of connotative, ideological, and cultural meanings in the text. This study concludes that the integration of balaghah and semiotics approaches can enrich the interdisciplinary method of Qur'anic interpretation. In addition, this approach also offers a hermeneutic alternative that is more responsive to contemporary social and intellectual dynamics.